Procedure for Out of Court Settlement of Consumer Disputes before the Passenger Ombudsman - Zawacka-Klonowska, Dominika (Review of European and Comparative Law, 2020)
The adoption of Directive 2013/11/EU of the European Parliament and of the Council of 21.05.2013 on alternative dispute resolution methods for the settlement of consumer disputes and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC and Regulation (EU) No 524/2013 of the European Parliament and of the Council of 21.05.2013 on the online system of consumer disputes resolution and amending Regulation (EC) No 2006/2004 and Directive 2009/22/EC, was intended to enable consumers to resolve disputes with entrepreneurs using alternative dispute resolution methods. In order to ensure that consumers can exercise the rights granted to them by EU law, by way of implementation of the Regulations there has been an amendment of the Act of 3 July 2003 - Aviation law (i.e. Journal of Laws of 2019, item 1580), on the basis of which the institution of the Passenger Ombudsman at the Civil Aviation Office was established, which is an entity entitled to conduct proceedings for the out-of-court settlement of consumer disputes between a passenger and an air carrier, tour operator, or seller of air tickets, entered into the register of entitled entities. The purpose of this study is to present the legal regulation concerning proceedings before the Ombudsman, indicating the political position of the Passenger Ombudsman and his team using analytical and comparative research methods.